GENOTYPE-PHENOTYPE CORRELATIONS OF THE COURSE OF CYSTIC FIBROSIS IN RUSSIAN CHILDREN. THE FIRST DESCRIPTION OF ELEVEN NEW MUTATIONS - Yulia V. Gorinova; Kirill V. Savostyanov; Alexandr A. Pushkov; Alexey G. Nikitin; Evgeniy L. Pen'kov; Stanislav A. Krasovskiy; Olga I. Simonova; L. S. Namazova-Baranova ("Paediatrician" Publishers LLC, 2018)
Background. Cystic fibrosis is a hereditary disease that occurs as a result of mutations in the regulator gene of chloride ion transmembrane transport (CFTR). Finding mutations in the CFTR gene is necessary for identification of the clinical features of cystic fibrosis.Objective. Our aim was to identify genotype-phenotype correlations between mutations of the first class of pathogenicity and clinical manifestations of cystic fibrosis based on studying the prevalence and structure of CFTR gene mutations.Methods. The study included children under 18 years with cystic fibrosis admitted to hospital between 2013 and 2017. Biallelic mutations in the CFTR gene were the noninclusion criterion. The CFTR gene variants were analyzed by next-generation sequencing method.Results. In 125 patients with cystic fibrosis, 59 different variants of the CFTR gene were detected, 11 of them not previously described. The most common was the deletion c.1521_1523del found in 98 (39.2%) of the 250 analyzed CFTR gene alleles and the deletion c.1545_1546del found in 22/250 (8.8%) alleles. It has been shown that the mutation c.1545_1546del, p.Y515* was more often found in children of the Chechen nation - odds ratio (OR) 139 (95% confidence interval 15-1,257). It has been established that meconium ileus, pancreatic deficiency and cirrhosis are more common in patients with mutations of the first category of pathogenicity: OR 3.9 (95% CI 1.0-15.0), 4.4 (95% CI 1.8-11.1), and 351 (95% CI 17.5-7,046), respectively. The association of CFTR gene mutations with the development of bronchiectases and polypous pancinusitis has not been found.Conclusion. Correlations between the genotype and clinical manifestations of cystic fibrosis in Russian children with CFTR gene mutations of the first class of pathogenicity have been established.